(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
The purpose of this study is to examine how the incentive system affects human resource empowerment, with a particular emphasis on the monetary and moral incentives that are a part of it. It also looks at how this system affects its aspects and turns empowerment into an organizational and strategic culture, helping to build and establish a culture of human resource empowerment within organizations. The main instrument for gathering data and information for the study was a questionnaire that was given to a sample of thirty-two participants and statistically with spss V26. According to the empirical study, Algeria Telecom’s incentive structure significantly influenced and empowered its people resources. The results show that there is a statistically significant correlation between material and moral incentives and their impact on Algeria Telecom’s human resource empowerment at the significance level (α < 0.05). The study suggests appreciating the incentive system and keeping it updated and improved throughout time. Keywords: Algeria Telecom; economic institution; human resource empowerment; monetary and moral rewards; incentive scheme.